Introduction to the Deep Convective Clouds and Chemistry (DC3) 2012 Studies. Issue 14 (29th July 2019) - Barth, M. C.; Rutledge, S. A.; Brune, W. H.; Cantrell, C. A.
Abstract: The Deep Convective Clouds and Chemistry (DC3) project aimed to determine the impact of deep, midlatitude continental convective clouds on tropospheric composition and chemistry. The DC3 field campaign was conducted over a broad area of the central United States during May–June 2012. Data collected by DC3 have been extensively analyzed, with many results published in Deep Convective Clouds and Chemistry 2012 Studies (DC3), a joint special section of JGR Atmospheres and Geophysical Research Letters . This paper highlights key results from the DC3 project as an introduction to the special issue. Key Point: Key findings from the DC3 project on convective transport, chemistry, lightning, and cloud physics are summarized